Digital Tax Systems Transform Municipal Collection Efficiency in Caribbean Colombian Cities Through Technological Innovation and Administrative Modernization - Mario de la Puente; Jose Torres; Hernan Guzman; Heidy Rico; Daniela Navarro (Public Finance and Management, 2026)
This study analyzes the impact of digital tax management systems on municipal collection efficiency across three major Caribbean Colombian cities from 2013 to 2023. Using autoregressive integrated moving average (ARIMA) intervention models, fixed effects panel regression, and difference-in-differences estimation with longitudinal data from Barranquilla, Cartagena, and Santa Marta, the research finds consistent positive effects of digitalization on tax collection performance. Results show that digitalization increases municipal tax collections by 8.9 to 15.6 percentage points, representing substantial improvements in fiscal revenue generation following digital system implementation. The analysis controls for economic and demographic factors while employing rigorous data validation procedures including Benford’s law testing and inter-institutional concordance analysis. These findings contribute empirical evidence on subnational tax digitalization in developing countries, supporting the hypothesis that technological modernization enhances municipal fiscal capacity through improved administrative processes and taxpayer compliance mechanisms.